THE ROLE OF DIGITAL MARKETING IN EFFORTS TO DEVELOP TECHNOLOGY-BASED MSMES IN SENGKOTEK SAMARINDA VILLAGE - Sayid Irwan (Jurnal Ekonomi, 2023)
The development of Micro, Small and Medium Enterprises (MSMEs) has stagnated during the Covid-19 pandemic. There are so many MSMEs experiencing a decline in sales and cannot develop and even almost go bankrupt. This condition makes MSME actors have to think about being able to survive for the continuity of their business. During the Covid-19 pandemic, many consumers reduced interactions outside the home by maintaining distance to break the chain of spread of the Covid-19 virus. MSME players can continue their business while still meeting consumer needs during the pandemic by shifting purchases online. The shift from offline purchases to online (digital) will make it easier for MSME players to expand marketing access. The role of digital technology has a significant influence on MSMEs. The emerging technological paradigm utilizes the potential of stronger and more sustainable MSMEs. Social media and E-commerce can be a forum for selling MSME actors. It is known that MSME players have not followed digital developments optimally, especially due to lack of knowledge about digital marketing. The purpose of the community empowerment program for MSMEs in Sengkotek Village is to provide digital marketing training assistance as an effort to develop and expand technology-based (digital) marketing networks. After carrying out this service, it is hoped that MSME actors in Sengkotek Village will continue to synergize for the sustainability of MSMEs and the economic development of the community.